Nature’s sophisticated architecture: a strategic approach for protein-polysaccharide complexes to address the “shelf-life vs. bioavailability” dilemma of polyphenols in food applications - Qu, Shen; Bai, Hua; Xu, Yan; Li, Borui; Wang, Xinna (Frontiers in Nutrition, 2025)
Polyphenols exhibit significant potential as functional food ingredients owing to their pronounced health-promoting effects. However, their practical application is substantially limited by a central technological dilemma: the trade-off between chemical instability during food processing and storage, and low bioavailability within the human gastrointestinal tract. This review focuses on a nature-derived, biocompatible, and sustainable strategy to address this challenge, which involves the use of molecular self-assembly between proteins and polysaccharides to construct nano- or micro-scale delivery systems. We systematically elucidate how these natural biopolymer complexes, through their sophisticated structural designs, offer a promising solution to mitigate the aforementioned dilemma. The review provides an in-depth analysis of two core fabrication mechanisms—complex coacervation and layer-by-layer (LbL) electrostatic deposition. It highlights how these structures, via functional stratification, not only provide a physical barrier to protect polyphenols from environmental stressors in complex food matrices but also confer the ability for smart release in response to specific physiological signals in the digestive tract, such as pH shifts and enzymatic digestion. Finally, we assess the feasibility and challenges of translating this technology from the laboratory to industrial-scale production, emphasizing its unique advantages in developing “clean label” functional foods. Future perspectives on precise structural control, multifunctional co-delivery, and interactions with gut microbiota are also discussed.